2017
DOI: 10.1080/16549716.2017.1330858
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in running a complex electronic data capture system using mobile phones in a large-scale population trial in southern Nepal

Abstract: The increasing availability and capabilities of mobile phones make them a feasible means of data collection. Electronic Data Capture (EDC) systems have been used widely for public health monitoring and surveillance activities, but documentation of their use in complicated research studies requiring multiple systems is limited. This paper shares our experiences of designing and implementing a complex multi-component EDC system for a community-based four-armed cluster-Randomised Controlled Trial in the rural pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Between 2013 and 2015, more than 60,000 women were enrolled into menstrual monitoring and more than 25,000 pregnancies were detected. The details of the trial surveillance system have been reported elsewhere (Style et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2013 and 2015, more than 60,000 women were enrolled into menstrual monitoring and more than 25,000 pregnancies were detected. The details of the trial surveillance system have been reported elsewhere (Style et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A household census conducted in 2013 before the start of the intervention identified married women between 10 and 49 years of age who had not had operative family planning and whose husbands had not had a vasectomy. These were asked to consent to take part in the trial surveillance system which identified new pregnancies over the course of the trial, a 'menstrual monitoring system' (Style et al, 2017). As discussed in Section 2, in all intervention areas, women's groups practising PLA were open to all community members to attend, but cash and food transfers were only provided to consenting pregnant women from the third month of pregnancy until the end of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Field surveys, traditionally conducted on paper forms, are increasingly using electronic data capture tools, such as tablets and smartphones. Compared with paper methods, commonly cited relative benefits of electronic data capture include quicker access to data, more options to check data quality and interviewer performance, lower costs for data entry, and reduced risk of data loss during transport and storage (1)(2)(3) .…”
mentioning
confidence: 99%
“…The use of electronic data collection, via mobile phones or tablets, has recently gained attention. Several studies have shown its advantages over paper-based data collection [2,3]. Other studies have shown it is also feasible, in LMICs, to collect dietary data via electronic data capture [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient intakes presented as median (25-75th percentile interquartile range) 2. Somers' D test-adjusted for cluster sampling.…”
mentioning
confidence: 99%